2007
DOI: 10.4037/ajcc2007.16.6.568
|View full text |Cite
|
Sign up to set email alerts
|

Skin Integrity in Critically Ill and Injured Children

Abstract: Background Skin breakdown increases the cost of care, may lead to increased morbidity, and has negative psychosocial implications because of secondary scarring or alopecia. The scope of this problem has not been widely studied in critically ill and injured children. Objectives To determine the incidence of skin breakdown in critically ill and injured children and to compare the characteristics of patients who experience skin breakdown with those of patients who do not. Methods Adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 10 publications
1
32
2
3
Order By: Relevance
“…Pressure ulcers are associated with prolonged hospital stay and increased risk of secondary infection . The financial burden associated with hospital‐acquired pressure ulcers is also not insignificant, with an estimated treatment cost of $11 billion every year . In 2008 the Centers for Medicare & Medicaid Services (CMS) suggested that hospital‐acquired pressure ulcers should be minimized, which may also affect Medicare and Medicaid reimbursement .…”
Section: Discussionmentioning
confidence: 99%
“…Pressure ulcers are associated with prolonged hospital stay and increased risk of secondary infection . The financial burden associated with hospital‐acquired pressure ulcers is also not insignificant, with an estimated treatment cost of $11 billion every year . In 2008 the Centers for Medicare & Medicaid Services (CMS) suggested that hospital‐acquired pressure ulcers should be minimized, which may also affect Medicare and Medicaid reimbursement .…”
Section: Discussionmentioning
confidence: 99%
“…17 Mechanical ventilation and a respiratory diagnosis are associated with higher risk of DRPU in this population. 18 In newborns, devices may severely a ect and distort nasal cartilage. e incidence of PU in paediatric patients may be as high as 28%, with non-invasive mechanical ventilation associated with PU formation (relative risk ratio 12.24).…”
Section: A Note On Terminologymentioning
confidence: 99%
“…Among the various studies of PU epidemiology (2,(15)(16)(17)(18)(19) . Baldwin found an incidence rate of 0.29% in a nationwide U.S. study of hospitalized or non-hospitalized children (2) .…”
Section: Discussionmentioning
confidence: 99%
“…The more immature the child and the more critical its condition, the less tolerant the skin and underlying structures and, consequently, the higher the risk of pressure sores (14,15) . Studies conducted in the U.S. pediatric population have revealed a prevalence of PUs ranging from 0.47% to 17% (4,(16)(17)(18) .…”
Section: Introductionmentioning
confidence: 99%